Kerjasama Guru dan Orang Tua dalam Membiasakan Perilaku Mandiri pada Anak di TK Al-huda Kec. Kota Selatan Kota Gorontalo - Sri Melianty Aliwu; Nurhayati Tine; Nunung Suryana Jamin (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
The purpose of this study is to explore "Teacher-Parent Collaboration in Fostering Independent Behavior in Children at TK Al-Huda Kindergarten, Kota Selatan District, Gorontalo City." This study used a descriptive qualitative method, with participants including the principal, teachers, parents, and children. Data was collected through interviews, observations, and documentation. Findings indicated that efforts to instill independent behavior in children remained limited and unstructured. Communication between teachers and parents typically occurred through regular meetings, lacking in-depth discussion or specific strategies. Teachers conveyed independence-related rules, such as eating independently and tidying up toys, but there was no structured program to support independence systematically. Observations showed positive development in some areas, such as independent activities and socialization, though some children still required guidance in emotional regulation and empathy. Clearer programs and guidelines optimize teacher-parent collaboration to foster children's independence better.